Response of rice pollen to water stress during anthesis - Puteh, Adam; Jali, Normaliana; Mohamad, Rosli; Shamsudin, Nuzuliati (2008)
Oryza sativa L. varieties MR84 and MR219 and weedy rice strains from Seberang Perak, Kuala Pilah and Tanjung Karang were observed for differences in general pollen morphology when subjected to water stress during anthesis on pollen aperture size. In general, no apparent difference in pollen morphology was observed between cultivated varieties and the weedy stains, both had isodiametric aperture with 5.7 µm in diameter. Tanjung Karang strain, however, had a slightly bigger aperture size. Water stressed the plants during anthesis resulted in greater reduction in pollen aperture size in the study indicated that weedy rice strains seemed able to withstand water stress better during anthesis compared to the cultivated rice varieties.